Regression Discontinuity in Serial Dictatorship: Achievement Effects at Chicago's Exam Schools - AbdulkadIroğlu, Atila; Angrist, Joshua D.; Narita, Yusuke; Pathak, Parag A.; Zarate, Roman A. (American Economic Review, 2017)
Many school and college admission systems use centralized mechanisms to allocate seats based on applicant preferences and school priorities. When tie-breaking uses non-randomly assigned criteria like distance or a test score, applicants with the same preferences and priorities are not directly comparable. The non-lottery setting does generate a kind of local random assignment that opens the door to regression discontinuity designs. This paper introduces a hybrid RD/propensity score empirical strategy that exploits quasi-experiments embedded in serial dictatorship, a mechanism widely used for college and selective K-12 school admissions. We use our approach to estimate achievement effects of Chicago's exam schools.